The Protective Effect of Zinc on Salt Induced Histological Changes in Femur of Sprague Dawley Rats-Data Driven Approach - Kaukab Anjum, Nomana Mahmood, Uzma Shahid, Shazia Imran, Maleeha Bano, Sumaira Abbasi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Osteoporosis, a degenerative skeletal illness, is a widespread medical issue that can affect a person's way of life. Aim: To evaluate how salt played a protective role in the Sprague Dawley rats' femur's microscopic alterations. Study Design: Random control trial Methodology: The study used 30 female, Sprague Dawley rats aged between 0 and 12 weeks. Three groups of the animals were randomly chosen. For eight weeks, group B rodents received a high salt diet supplemented with zinc (50 mg/kg/day), while group A rats were administered a high salt diet (8% NaCl). The control group's diet was left unaltered. The left femora of the rats were excised during dissection. There was a decalcification process. To quantify the cortical bone, tissue from the mid-shaft of the femur was taken. To acquire five micrometer (m) sections, processing was done. Hematoxylin and Eosin (H&E) was used to stain tissues as a histological parameter. Each group was compared to the others. Statistical analysis: MATLAB was used to conduct the data analysis. Mean+ S.D. was used to express quantitative data. For group comparisons, a 2-sample t-test was used. Statistical significance was defined as p 0.05. Results: Group A of the experimental study had a considerably smaller area of cortical bone from the mid shaft of the femur. When compared to group A, the experimental zinc-administered group B showed statistically significant improvements. Practical Implication: Osteoporosis is a multifactorial disease and numerous micro/macro nutrients and dietary components can influence bone health including high salt intake. Zinc plays a pivotal role in maintenance and growth of skeletal system and its deficiency results in growth failure, epidermal, gastrointestinal, central nervous, immune, skeletal, and reproductive systems disorders so present study was planned. Conclusion: A diet high in salt caused bone loss due to a reduction in the cortex's surface area. By promoting osteoblast activity and preventing bone-resorbing cells, zinc is useful in reducing the negative effects of salt on bones. Keywords: Cortex, Femur, Osteaoprosis, Salt and Zinc.